(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
The integration of technology tools into classrooms is a growing trend worldwide. Research studies indicate that technological tools are crucial in creating an environment in which students play an active role in the learning process. The Saudi Arabia government has heavily invested in the Information and Communication Technology (ICT) field, but is yet to fully benefit from the investment. There are a myriad of enablers and hindrances affecting the successful implementation of ICT in Saudi schools. Successful implementation of ICT can be realised through the promotion of constructivist learning environment. This study utilised mixed methodology approach in collecting data from teachers to evaluate the factors affecting effective ICT implementation in Saudi secondary schools. The factors affecting the practical use of educational technology include lack of management and technical support, time limitations, lack of ICT and pedagogical training, negative attitudes and beliefs towards educational technology, lack of clear policies and strategies on ICT adoption in learning institutions and resistance to change and inadequate technological resources. No single factor is capable of guaranteeing the successful ICT implementation in schools; therefore, a multifaceted approach is needed.